2012
DOI: 10.1002/da.21923
|View full text |Cite
|
Sign up to set email alerts
|

Group Cognitive and Behavioral Therapy and Bibliotherapy for Hoarding: A Pilot Trial

Abstract: This study provides support for the efficacy of GCBT for hoarding. The effect of adding nonclinician home assistance was not significant in this small sample. BIB was not sufficient to improve hoarding symptoms. The findings have implications for a stepped care model for treating hoarding (e.g., the benefits of psycho-education via BIB, added benefits of extra in-home visits) and suggest the need to further examine the role of in-home hoarding coaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 36 publications
(70 reference statements)
8
85
1
1
Order By: Relevance
“…Both clinician-rated and self-report symptom rating scales were used, an important issue in assessing symptoms of a disorder known to be frequently characterized by poor insight (Pertusa et al 2010, Neziroglu et al 2012). The subject sample had moderate to severe symptoms at baseline, with pre-treatment UHSS scores (24.4 +/− 3.9) similar to those found in the paroxetine study (Saxena et al 2007), and SI-R scores (68.8 +/− 9.9) that were slightly higher than those of multiple prior samples of compulsive hoarding subjects in CBT and support group studies, which have ranged from 59–67 (Steketee et al 2000, Tolin et al 2007, Muroff et al 2009, Muroff et al 2010, Steketee et al 2010, Gilliam et al 2011, Frost et al 2011, Frost et al 2012, Muroff et al 2012). Both self-report and clinician-administered hoarding severity rating scales demonstrated clinically and statistically significant improvements in hoarding symptom severity with treatment.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Both clinician-rated and self-report symptom rating scales were used, an important issue in assessing symptoms of a disorder known to be frequently characterized by poor insight (Pertusa et al 2010, Neziroglu et al 2012). The subject sample had moderate to severe symptoms at baseline, with pre-treatment UHSS scores (24.4 +/− 3.9) similar to those found in the paroxetine study (Saxena et al 2007), and SI-R scores (68.8 +/− 9.9) that were slightly higher than those of multiple prior samples of compulsive hoarding subjects in CBT and support group studies, which have ranged from 59–67 (Steketee et al 2000, Tolin et al 2007, Muroff et al 2009, Muroff et al 2010, Steketee et al 2010, Gilliam et al 2011, Frost et al 2011, Frost et al 2012, Muroff et al 2012). Both self-report and clinician-administered hoarding severity rating scales demonstrated clinically and statistically significant improvements in hoarding symptom severity with treatment.…”
Section: Discussionsupporting
confidence: 62%
“…In published CBT trials, improvement in compulsive hoarding symptoms, measured by decline in mean SI-R score, has ranged from 10–30% for group CBT (Steketee et al 2000, Muroff et al 2009, Muroff et al 2010, Gilliam et al 2011, Muroff et al 2012) to 27–28% for individual CBT (Tolin et al 2007, Steketee et al 2010). However, in the present study, treatment with venlafaxine extended-release resulted in a 32% mean improvement on the SI-R and 36% on the UHSS, while in the previous paroxetine study, mean symptom improvement was 31% for completers and 24% for the entire sample in an intent to treat analysis (Saxena et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Klontz and Klontz (2009) advocated resolving unfinished business associated with trauma as an approach to the treatment of money disorders (including compulsive hoarding) using an intensive group experiential therapy approach that has garnered some empirical support for its clinical utility (Klontz, Bivens, Klontz, Wada, & Kahler, 2008). Muroff, Steketee, Bratiotis, and Ross (2012) also found that weekly group cognitive behavior therapy sessions, along with non-clinician home visits over a 20 week period, showed significant reductions in hoarding symptoms.…”
Section: Interventionmentioning
confidence: 99%
“…Some variations of CBT have been also developed, including CBT with bibliotherapy [29], CBT with cognitive rehabilitation [30] CBT with motivational interviewing [31], CBT with internet supported group [32] and isolated bibliotherapy [33][34][35]. In conclusion, these studies reveal that there are a percentage of hoarders who do not benefit the current CBT approaches.…”
Section: Methods Based On Cbtmentioning
confidence: 99%